Chimo, a smokeless tobacco preparation, is associated with a higher frequency of type 2 diabetes. - González-Rivas, Juan P.; Nieto-Martínez, Ramfis; García Santiago, Raúl; Ugel, Eunice; Mechanick, Jeffrey I. (Investigación Clínica, 2017)
Ver Resumen PDF.